Young Lives: Vietnam Round 2 Survey - Le, T; Nguyen, P; Tran, M; Nguyen, V; Vo, T (Young Lives, 2008)
This report presents initial findings from the second round of data collection which was carried out in Vietnam in late 2006 to early 2007. It does not aim to give a comprehensive overview of all the findings from Young Lives, rather it gives a broad outline of some of the key indicators of childhood poverty and changes that have taken place in the children’s lives between the first round of data collection in 2002 and this second round. Data are mainly presented for the entire age group cohort, in most cases separated into wealth groups or by rural/urban location. The full richness of the data is not reflected in this preliminary report, but we hope that it contains enough information to prompt other researchers, policymakers and stakeholders to start to engage with the data. Vietnam has achieved impressive progress in improving child outcomes. Poverty levels and maternal health figures already meet the standards set by the MDGs, and progress towards achieving the education goal is well underway. However, child malnutrition and access to sanitation and safe water remain a concern, as do stark disparities in outcomes between ethnic groups and rural and urban areas. The discussion and analysis presented in this report, although preliminary, give important insights into trends between the two rounds of research, key factors affecting children in Vietnam and the extent of inequalities between children of different groups. The analysis enables us to pinpoint policy implications for tackling childhood poverty in Vietnam as well as important and interesting avenues for future research. The data reflect the growth and poverty reduction witnessed in recent years and there is evidence that the Young Lives households have become better off over the four years of the survey. However, national inequalities in wealth, consumption expenditure and the incidence of poverty between urban and rural areas and between ethnic minorities and the majority group are reflected in the sample. These disparities fell slightly between the two rounds but remained prominent in 2006.